2005
DOI: 10.1289/ehp.7649
|View full text |Cite
|
Sign up to set email alerts
|

Domoic Acid Transfer to Milk: Evaluation of a Potential Route of Neonatal Exposure

Abstract: Domoic acid (DA), produced by the diatom genus Pseudo-nitzschia, is a glutamate analog and a neurotoxin in humans. During diatom blooms, DA can contaminate filter-feeding organisms, such as shellfish, and can be transferred by ingestion to higher trophic levels. Several intoxication events involving both humans and various marine mammals have been attributed to DA. Affected organisms show neurological symptoms such as seizures, ataxia, headweaving, and stereotypic scratching, as well as prolonged deficits in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 28 publications
2
44
0
Order By: Relevance
“…Thus it is possible that in exposed cases where the sea lion foetus survives to birth, exposure to the toxin in utero could result in developmental abnormalities leading to neurological and behavioural deficits as the animals age. Additionally, neonatal sea lions may be exposed to the toxin after birth by exposure in milk, which has been demonstrated to be possible in rats (Maucher & Ramsdell 2005). Further work is warranted to examine the effects of domoic acid on brain development as well as association between behavioural abnormalities and hippocampal and extra-hippocampal lesions in sea lions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus it is possible that in exposed cases where the sea lion foetus survives to birth, exposure to the toxin in utero could result in developmental abnormalities leading to neurological and behavioural deficits as the animals age. Additionally, neonatal sea lions may be exposed to the toxin after birth by exposure in milk, which has been demonstrated to be possible in rats (Maucher & Ramsdell 2005). Further work is warranted to examine the effects of domoic acid on brain development as well as association between behavioural abnormalities and hippocampal and extra-hippocampal lesions in sea lions.…”
Section: Discussionmentioning
confidence: 99%
“…Urine and serum samples submitted for domoic acid testing were screened by direct competitive domoic acid ELISA (Biosense Laboratories, Bergen, Norway), and positive samples were confirmed by liquid chromatography-tandem mass spectrometry (LC-MS/MS; Van Dolah et al 1997;Maucher & Ramsdell 2005). Faeces were examined for toxic P. australis diatoms by scanning electron microscopy and positive samples were tested for domoic acid using high-performance liquid chromatography (HPLC; Lefebvre et al 1999).…”
Section: Methodsmentioning
confidence: 99%
“…Domoic acid has also been shown to readily cross the placenta in experimentally exposed rat models (Dakshinamurti et al, 1993;Levin et al, 2005). It has been hypothesized that the nonkeratinized skin of the fetus facilitates transfer of the toxin by providing a poor barrier to the toxin after absorption into the amniotic fluid (Maucher and Ramsdell, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Although we did not account for maternal transfer of DA to pups via lactation, we suspect that this is an important mechanism for DA transfer particularly in newborn pups (not included here) whose energy demands are supplied entirely through milk. Studies in rats (Maucher & Ramsdell 2005) found measurable DA in milk of lactating females and showed that pups exposed to DA-spiked milk had measurable amounts of DA in plasma, indicating that this biotoxin is transferable from exposed mothers to lactating pups. DA transfer through lactation in sea lion pups could be evaluated as additional information becomes available.…”
Section: Discussionmentioning
confidence: 99%